Modeling Tsunamis Generated by Submarine Landslides at Stromboli Volcano (Aeolian Islands, Italy): A Numerical Benchmark Study - Esposti Ongaro, Tomaso; de' Michieli Vitturi, Mattia; Cerminara, Matteo; Fornaciai, Alessandro; Nannipieri, Luca; Favalli, Massimiliano; Calusi, Benedetta; Macías, Jorge; Castro, Manuel J.; Ortega, Sergio; González-Vida, José M.; Escalante, Cipriano (Frontiers in Earth Science, 2021)
We present a study aimed at identifying the most effective modelling approach for tsunami generation, propagation and hazard in an active volcanic context, such as the island of Stromboli (Italy) where: 1) the tsunami source conditions are difficult to predict, to observe and to model; 2) the source of the tsunami is close to the shoreline; and 3) the bathymetry is very steep and irregular. Several models, at different levels of approximation and accuracy, have been compared in this study: the NHWAVE three-dimensional non-hydrostatic model in sigma-coordinates and the HySEA family of geophysical codes. In particular, different instances of the Multilayer-HySEA model with one or more layers, in hydrostatic and non-hydrostatic formulation and with different landslide models have been tested. Model results have been compared for the maximum runup along the shores of Stromboli village, and the waveform sampled at four proximal sites (two of them corresponding to the locations of the monitoring gauges, offshore the Sciara del Fuoco). Both rigid and deformable (granular) submarine landslide models, with volumes ranging from 7 to 25 million of cubic meters, have been used to trigger the water waves, with different physical descriptions of the mass movement. Close to the source, the maximum surface elevation and the resulting runup at the Stromboli village shores obtained with hydrostatic and non-hydrostatic models are similar. However, hydrostatic models overestimate the initial positive wave crest, whose height increases with the distance. Moreover, as expected, results indicate significant differences between the waveforms produced by the different models at proximal locations. Such an aspect is particularly critical in the perspective of using proximal sea-level gauges installed at Stromboli to characterize tsunami source in an early-warning system. We show that the use of non-hydrostatic models, coupled with a multilayer approach, allows a better description of the waveforms. However, the source description remains the most sensitive (and uncertain) aspect of the modeling. We finally show that non-hydrostatic models such as Multilayer-HySEA, solved on accelerated GPU architectures, exhibit the optimal trade-off between accuracy and computational requirements, for the envisaged problem size, to simulate the proximal wave field generated by volcano landslides.